Methods for public sector institution strategic planning: theoretic potential and perspectives - Bivainis, Juozas; Tunčikienė, Živilė (Business: Theory and Practice, 2006)
In pursuance of effective strategic activity plan preparation methods which could express institutions rational strategic planning model should be used. Extensive theoretic potential for institution strategic planning and sufficient abilities to use it together are guarantee for reaching goals of institution’s strategic planning. On the other hand, the question arises whether the use of theoretic potential allows to reach goals of rational strategic planning? The solution of our suggested complex tasks of institution’s rational strategic planning is to set the demand of the institution’s activity development and this demand fulfillment opportunities and weaknesses, to detect the directions and priorities of institution’s activity development, to chose the best ways and means to implement the institution’s activity development directions and priorities, to monitor the institution’s activity development means implementation. The analysis and evaluation of methods are purposeful to perform in the elements section of the complex of the planning tasks. Generally combinations of methods to solve institution’s strategic analysis tasks in special literature are recommended. The use of combinations of methods allows analyzing and evaluating different factors which influence development of institution’s activity, plus synthesizes the results. The use of theoretic potential for institution’s objective orientation setting creates preconditions to form the mission of institution, create the vision and set strategic goals. Theoretic potential for preparation and acceptance of institution’s strategic decisions are sufficient for decision of tasks of alternatives generation, formation of criteria for alternatives evaluation along with the criteria combination, alternatives analysis and evaluation, the best alternative choice. The use of the institution’s action plan implementation monitoring theoretic potential creates preconditions for analysis and evaluation of inside changes which happened due to action plan implementation, for setting connections between action plan implementation results and institution’s activity development indicators. The use of methods recommended in special literature doesn’t create preconditions to generate alternatives of rational action plan, i.e. to generate alternatives integrating the actions for increasement of the allocation of institutions resources, usage and development possibilities. In regard to complexity principle formation the criteria to evaluate the action plan alternatives and to form criteria combinations is problematical too. Moreover, suggested recommendations to analyse and evaluate action plan alternatives aren’t concretized to the level of quantitative analysis and evaluation of alternatives. So methods analysis and evaluation in context of tasks of institution rational strategic planning allow to identify strong and weak aspects of these tasks decision. Besides, it enables to make methods selections for institution strategic analysis, objective orientation setting, strategic decision preparation and acceptance, monitoring of actions plan implementation. Application of methods selections creates preconditions for decision of adequate strategic planning tasks. In pursuance to fill the essential gap in institution’s strategic planning directions for improvement of planning of institution’s strategic decisions implementation are established. Its implementation allows to reach all goals of rational strategic planning.Article in Lithuanian.Viešojo sektoriaus institucijų strateginio planavimo metodai: teorinis potencialas ir perspektyvosSantrauka. Išanalizuotas ir įvertintas viešojo sektoriaus institucijų strateginio planavimo uždavinių sprendimo teorinis potencialas. Esamą teorinį potencialą galima produktyviai naudoti šiems institucijų strateginio planavimo uždaviniams spręsti: strateginei analizei atlikti, tikslinei orientacijai nustatyti, strateginiams sprendimams rengti ir priimti, veiksmų plano įgyvendinimo monitoringui vykdyti. Išvardytiems institucijų strateginio planavimo uždaviniams spręsti sudaryti metodų rinkiniai ir pateiktos rekomendacijos jiems taikyti. Atsižvelgiant į metodų analizės rezultatus konstatuojama, kad silpniausia institucijų strateginio planavimo grandinės grandis yra strateginių sprendimų įgyvendinimo veiksmų plano rengimo metodinės priemonės. Siekiant pašalinti nustatytas metodinio pobūdžio spragas institucijų strateginio planavimo uždavinių sprendimo grandinėje, parengtos rekomendacijos strateginių sprendimų įgyvendinimo planavimo metodinėms priemonėms sukurti.Reikšminiai žodžiai: institucija, strateginis planavimas, metodai, analizė, taikymas.